Design of a light and Ca2+ switchable organic-peptide hybrid - Zinah hilal khaleel; No, Young Hyun; Kim, Nam Hyeong; Bae, Do Hyun; Wu, Yibing; Kim, Suhueon; Choi, Hojae; Lee, Da Eun; Jeong, Se yun; Ko, Yoon-Joo; Kim, Seong-Gi; Suh, Minah; et al. (National Academy of Sciences, 2025)
The design of organic？peptide hybrids has the potential to combine our vast knowledge of protein design with small molecule engineering to create hybrid structures with complex functions. Here, we describe the computational design of a photoswitchable Ca2+-binding organic？peptide hybrid. The designed molecule, designated Ca2+-binding switch (CaBS), combines an EF-hand motif from classical Ca2+-binding proteins such as calmodulin with a photoswitchable group that can be reversibly isomerized between a spiropyran (SP) and merocyanine (MC) state in response to different wavelengths of light. The MC/SP group acts both as a photoswitch as well as an optical sensor of Ca2+ binding. Photoconversion of the SP to the corresponding MC unmasks an acidic phenol, which CaBS uses as an integral part of both its Ca2+-binding site as well as its tertiary and quaternary structure. By design, the SP state of CaBS is monomeric, while the Ca2+-bound form of the MC state is an obligate dimer, with two Ca2+-binding sites formed at the interface of a domain-swapped dimer. Thus, light and Ca2+ were expected to serve as an “AND gate” that powers a change in backbone structure/dynamics, oligomerization state, and fluorescence properties of the designed molecule. CaBS was designed using Rosetta and molecular dynamics simulations, and experimentally characterized by nuclear magnetic resonance, isothermal titration calorimetry, and optical titrations. These data illustrate the potential of combining small molecule engineering with de novo protein design to develop sensors whose conformation, association state, and optical properties respond to multiple environmental cues.